Contemporary management and outcomes for infants born with oesophageal atresia1. Issue 4 (18th January 2013) - Burge, D. M.; Shah, K.; Spark, P.; Shenker, N.; Pierce, M.; Kurinczuk, J. J.; Draper, E. S.; Johnson, P. R. V.; Knight, M.; ,
Abstract Background: Reports on the management and outcome of rare conditions, such as oesophageal atresia, are frequently limited to case series reporting single‐centre experience over many years. The aim of this study was to identify all infants born with oesophageal atresia in the UK and Ireland to describe current clinical practice and outcomes. Methods: This was a prospective multicentre cohort study of all infants born with oesophageal atresia and/or tracheo‐oesophageal fistula in 2008–2009 in the UK and Ireland to record current clinical management and early outcomes. Results: A total of 151 infants admitted to 28 paediatric surgical units were identified. Some aspects of perioperative management were universal, including oesophageal decompression, operative technique and the use of transanastomotic tubes. However, there were a number of areas where clinical practice varied considerably, including the routine use of perioperative chest drains, postoperative contrast studies and antireflux medication, with each of these being employed in 30–50 per cent of patients. There was a trend towards routine postoperative ventilation. Conclusion: The prospective methodology used in this study can help identify practices that all surgeons employ and also those that few surgeons use. Areas of clinical equipoise can be recognized and avenues for further research identified. Copyright © 2013 British Journal of Surgery Society Ltd. Published by John Wiley & Sons, Ltd.